Experimental and numerical study on honeycomb sandwich panels under bending and in-panel compression. (5th November 2017) - Sun, Guangyong; Huo, Xintao; Chen, Dongdong; Li, Qing
Abstract: Sandwich structures have been extensively employed as lightweight composite components in aerospace and shipbuilding engineering for their high capacity of stiffness, strength and energy absorption. To explore the crushing behaviors of honeycomb sandwiches, both three-point bending (TPB) and in-panel compression (IPC) tests were performed on aluminum honeycomb sandwich panels in this study. The effects of several key structural parameters on crashworthiness characteristics and collapse mechanism were first explored through the experiments here. The experimental results divulged that crashworthiness and collapse mode of sandwich structures were greatly influenced by the structural parameters under the TPB test. The crash behaviors can be also affected by both structural and adhesive parameters in the IPC test. Through validating with the experimental data, the numerical models were established to capture some deformation and failure details in the crushing processes. Taking into account the adhesive interface in the finite element (FE) model, glue debonding was simulated for the IPC loading, which is in good agreement with the experimental results at the skin panel buckling. Based on the experimental results, theoretical solutions for the TPB test were also established to predict the peak load, energy absorption and collapse mode. This study provided a new basis for the further studies on the crashworthiness optimization of sandwich structures. Graphical abstract: Highlight: Crashworthiness characteristics of honeycomb sandwiches were studied systematically. Honeycomb sandwiches collapsed in diverse modes with different structural parameters. Specific energy absorption of specimens under three-point bending test are sensitive to structural parameters of the core. Theoretical models were derived to predict the peak load, energy absorption and collapse mode under three-point bending test.